2013
DOI: 10.1016/j.appet.2013.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Observations of mealtimes in hospital aged care rehabilitation wards

Abstract: Version:This is the authors' final version of a work that was accepted for publication in Appetite. Changes resulting from the publishing process, such as editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication.http://www.canberra.edu.au/ University of Canberra, ACT 2601 Australia, Switchboard +61 2 6201 5111. The University of Canberra is located on Ngunnawal Country.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 25 publications
0
49
0
3
Order By: Relevance
“…However, in the present audit, a number of patients were not offered hospital snacks, although the reasons for this were not explored. A lack of hospital snack provision has been identified as an inhibitory factor of optimal nutrition and, although snacks are often available, some studies have found that this is not always communicated adequately to patients , which appeared to be the case in the present audit. The Digest emphasises that patients should be offered hospital snacks twice daily, rather than relying on patient's requests .…”
Section: Discussionmentioning
confidence: 90%
“…However, in the present audit, a number of patients were not offered hospital snacks, although the reasons for this were not explored. A lack of hospital snack provision has been identified as an inhibitory factor of optimal nutrition and, although snacks are often available, some studies have found that this is not always communicated adequately to patients , which appeared to be the case in the present audit. The Digest emphasises that patients should be offered hospital snacks twice daily, rather than relying on patient's requests .…”
Section: Discussionmentioning
confidence: 90%
“…Studies investigating mealtime assistance have acknowledged factors that inhibit success, including staff time pressures and/or availability (Heaven, Bamford, May, & Moynihan, 2013;Manning et al, 2012;Martinsen & Norlyk, 2012;Robison et al, 2015;Tsang, 2008;Walton et al, 2013) and communication of need for mealtime assistance (Manning et al, 2012;Robinson et al, 2002). Research exploring the patient viewpoint emphasises the need to overcome these barriers, identifying that patients are dissatisfied with the lack of mealtime support, yet are reluctant to ask for help (Naithani et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Patients value hospital food and its provision (Johns, Hartwell, & Morgan, ; Stanga et al., ), yet inadequate food intake is a common and complex problem in hospitals globally (Agarwal et al., ; Dupertuis et al., ; Hiesmayr et al., ). Research has identified individual, organizational and environmental factors that can have an impact on nutritional intake (Collins, Huggins, Porter, & Palermo, ; Kondrup et al., ; Ross, Mudge, Young, & Banks, ; Walton et al., ). Malnutrition is a consequence of poor nutritional intake and has been associated with increased morbidity, mortality, length of stay and healthcare costs (Correia & Waitzberg, ; Elia, Stratton, Russell, Green, & Pang, ; Watterson et al., ; White, Guenter, Jensen, Malone, & Schofield, ).…”
Section: Introductionmentioning
confidence: 99%